The Effect of Pantonime Games in Improving EFL Students’ Speaking Ability - Lestari, Inge Restu (Yayasan Darussalam Bengkulu, 2021)
Based on researcher observation, the students may be confused about what to speak although they know the topic which has been given by their teachers. They are confused to speak their ideas about the topic. They tend to difficult to memorizing vocabulary and error grammar because they do not interest in English learning. So, based on the students’ problem that they are faced, the writer wants to apply games in teaching English especially teaching speaking. The objective of the research is to see whether there is a significant effect of the use of pantomime game media on the speaking ability of the students. Based on the findings of research conducted in class VII at Junior High School Number 20 Bengkulu Selatan in Academic Year 2021/2022, the researcher can draw the following conclusions : 1) The average score in experimental class that used Pantonime Games is 76.2; while in the control class that only used teaching material derived from printed books without any auxiliary media and strategies are 74.5. Thus, it can be said that the experiment class showed a higher average result than the average score in the control class. 2) Pantonime Games to improving Students’ Speaking ability indicated by scores they get and from students’ responses to three meetings teach activities. It can be concluded that students enjoy the Pantonime Games. So, the researcher concludes that there is an effect on the Speaking Ability who teaches using Pantonime Games. This indicates that the research question has been answered.